2021
DOI: 10.1038/s41598-021-97853-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between increased circulating endothelial progenitor cell levels and anxiety/depressive severity, cognitive deficit and function disability among patients with major depressive disorder

Abstract: The association of major depressive disorder (MDD) with cardiovascular diseases (CVDs) through endothelial dysfunction is bidirectional. Circulating endothelial progenitor cells (cEPCs), essential for endothelial repair and function, are associated with risks of various CVDs. Here, the relationship of cEPC counts with MDD and the related clinical presentations were investigated in 50 patients with MDD and 46 healthy controls. In patients with MDD, a battery of clinical domains was analysed: depressed mood with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…Most findings have shown that lower cEPC numbers are associated with high depressive symptom severity and depressive disorder (N. Yang et al, 2021). However, a contradictory finding has also been reported (Liou et al, 2021 (Fiedorowicz et al, 2012). Because cEPCs are direct indicators of endothelial function (Chopra et al, 2018), the finding of an inverse correlation between manic symptom severity and cEPC numbers in present study is in accordance with the finding of Fiedorowicz et al (2012), and the finding suggests that endothelial dysfunction is associated with low cEPC numbers in patients with BPD.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Most findings have shown that lower cEPC numbers are associated with high depressive symptom severity and depressive disorder (N. Yang et al, 2021). However, a contradictory finding has also been reported (Liou et al, 2021 (Fiedorowicz et al, 2012). Because cEPCs are direct indicators of endothelial function (Chopra et al, 2018), the finding of an inverse correlation between manic symptom severity and cEPC numbers in present study is in accordance with the finding of Fiedorowicz et al (2012), and the finding suggests that endothelial dysfunction is associated with low cEPC numbers in patients with BPD.…”
Section: Discussionsupporting
confidence: 84%
“…Most findings have shown that lower cEPC numbers are associated with high depressive symptom severity and depressive disorder (N. Yang et al., 2021 ). However, a contradictory finding has also been reported (Liou et al., 2021 ; N. Yang et al., 2021 ), which may be explainable by variations in the study populations, the effect of antidepressants, or the duration of antidepressant treatment (Liou et al., 2021 ; N. Yang et al., 2021 ). Although studies have shown the association between depressive symptoms and depressive disorder, the relationship of the cEPC count with manic and related symptoms in BPD has not been studied.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[71][72][73] There is evidence of benefit after several psychological and psychiatric pharmacological and nonpharmacological interventions. [74][75][76]…”
Section: Mental Disordersmentioning
confidence: 99%